Green Accounting Adoption In Forestry Ministry: A Theory of Planned Behavior Case Study - Dwi Apriana; Khairudin Khairudin (Journal of Accounting Science, 2026)
General Background: Climate change demands transparent environmental reporting. Specific Background: Green Accounting (GA) is an instrument that aligns economic and environmental aspects in the financial reporting system, but the Ministry of Forestry, as a public sector, has not implemented it comprehensively. Knowledge Gap: Most research on GA has been conducted in the private sector, and none has revealed the readiness of GA implementation within the framework of the Theory of Planned Behaviour. Objective: To explore the  Ministry of Forestry's readiness to implement GA in the areas of regulation, human resources, and reporting systems, using the TPB framework. Methods: This research is qualitative, using a case-study approach through Focus Group Discussions (FGDs), in-depth interviews with policymakers, and expert judgment from environmental accounting experts. Results: The public sector is not yet ready to implement GA because formal policies and technical guidelines do not yet support it, while employee attitudes toward GA are positive. Novelty:  This study is the first application of TPB in the public sector in the context of environmental accounting, which also highlights the importance of regulations and technical guidelines for GA implementation. Implications: These findings emphasize the importance of government regulations and technical guidance for the implementation of GA in the public sector.